Allele‐Specific Expression at the RET Locus in Blood and Gut Tissue of Individuals Carrying Risk Alleles for Hirschsprung Disease. Issue 5 (15th March 2013) - Matera, Ivana; Musso, Marco; Griseri, Paola; Rusmini, Marta; Di Duca, Marco; So, Man‐ting; Mavilio, Domenico; Miao, Xiaoping; Tam, Paul HK; Ravazzolo, Roberto; Ceccherini, Isabella; Garcia‐Barcelo, Merce
<x xml:space="preserve">Abstract</x> We studied a well‐known HSCR (Hirschsprung disease; colon aganglionosis)‐associated RET risk haplotype that correlates with reduced RET expression. We investigated whether RET allele‐specific expression (ASE) could contribute to the overall reduction of RET mRNA detected in carriers of the risk haplotype. Comparison of RET expression levels between human gut samples with and without ASE, correlated reduced RET expression with preferential transcription from the risk haplotype. RET ASE occurred in ganglionic gut regardless of the disease status. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>